Gene expression patterns of the female genital tract and immunomodulation by Lactobacillus species - Abrahams, Andrea Gillian (Division of Medical Virology, 2020)
Inflammation in the female genital tract (FGT) is associated with increased HIV-1 viral replication, HIV-1 transmission and HIV-1 acquisition. The optimal commensal Lactobacillus bacterial species is associated with reduced inflammation in the FGT and dampened immune responses to non-optimal bacteria in vitro. Using a transcriptomics approach, this research aimed to investigate gene expression patterns in the FGT of HIV-infected women compared to peripheral blood. Furthermore, transcriptomics was used to investigate interactions between different vaginal Lactobacillus species and the host to elucidate its immunomodulatory mechanisms. Cervical cytobrushes and blood samples were collected from chronically HIV-infected South African women. Cervical and peripheral blood mononuclear cells (CMCs and PBMCs) were isolated and mRNA was extracted for microarray analysis using the Illumina HumanHT-12 v3 Expression BeadChip system. Eight Lactobacillus isolates, two of each L. jensenii, L. mucosae, L. crispatus and L. vaginalis species were included in this study. The effects of these lactobacilli on cytokine production by vaginal epithelial (VK2) cells stimulated with Gardnerella vaginalis (ATCC 14018) were tested in vitro, RNA was extracted and used for Affymetrix Genechip whole transcript microarray analysis. This study found that significantly over-expressed genes in CMCs compared to PBMCs were mapped to proinflammatory signaling pathways (including Nuclear factor kappa B (NFκB), Tumor necrosis factor (TNF), Toll-like receptor (TLR) and Nucleotide-binding and oligomerization domain (NOD)-like receptor). Concurrently, a signature of reduced potential for adaptive immunity was observed in CMCs compared to PBMCs, as evidenced by underrepresentation of the T cell receptor signaling and natural killer cell mediated cytotoxicity pathways. G. vaginalis induced a potent proinflammatory cytokine response by VK2 cells in vitro. Over-expressed genes in G. vaginalis-stimulated VK2 cells compared to unstimulated VK2 cells were mapped to inflammatory signalling pathways. In contrast, 3/8 Lactobacillus isolates, including two L. mucosae and one L. vaginalis species, reduced inflammatory cytokine production by VK2 cells in response to G. vaginalis and were thus termed “cytokinesuppressive”. Several genes, 7/8 of which are involved in inflammation, were downregulated in VK2 cells co-cultured with lactobacilli and G. vaginalis in combination compared to coculture with G. vaginalis only. Futhermore, when gene expression changes were investigated in cells cultured with cytokine-suppresive lactobacilli versus non-cytokine-suppressive lactobacilli, it was found that SAMD9L, DDX58, IFIT1 gene expression was downregulated exclusively in VK2 cells co-cultured with cytokine-suppressive lactobacilli and G. vaginalis compared to co-culture with G. vaginalis only. The findings of this study have identified distinct gene expression patterns in the FGT compared to peripheral blood. Furthermore, key genes that may play a critical role in the immunomodulatory effects of vaginal lactobacilli were identified, motivating for further confirmatory research.